Comprehensive Analysis of Financial Performance and Profit Growth Prediction of PT. Rizky Maharani Inhil 2019-2021 - Muchran, Muchriana; Masrullah, Masrullah; Palaguna, Andi Hilaluddin (Invoice : Jurnal Ilmu Akuntansi, 2024)
This study aims to comprehensively analyze the financial performance and predict the profit growth of PT. Rizky Maharani Inhil from 2019 to 2021 through the analysis of financial ratios. The data analyzed comprises the financial statements of PT. Rizky Maharani Inhil for the years 2019 to 2021. The company must maintain healthy and efficient financial performance to generate profits and enhance its achievements. The research method employed involves financial ratio analysis, including liquidity ratios, solvency ratios, profitability ratios, and activity ratios, along with Time Series Analysis to predict profit growth. The results of this study indicate that, based on the liquidity ratio proxied by the Current Ratio, the company's financial performance condition is favorable for profit growth. Similarly, the solvency ratio proxied by the Debt to Total Equity Ratio and the profitability ratio proxied by Net Profit Margin both show that the company's financial performance is conducive to profit growth. However, the activity ratio proxied by Total Assets Turn Over reveals that the company's financial performance is not favorable for profit growth.